Molecular modeling studies and in vitro screening of dihydrorugosaflavonoid and its derivatives against mycobacterium tuberculosis - Puranik, Ninad V.; Srivastava, Pratibha; Swami, Sagar; Choudhari, Amit; Sarkar, Dhiman (RSC Advances, 2018)
Novel drug regimens against tuberculosis (TB) are urgently needed and may be developed by targeting essential enzymes of Mtb that sustain the pathogenicity of tuberculosis. In the present investigation, series of compounds (5a-f and 6a-f) based on a naturally occurring rugosaflavonoid moiety were evaluated by in silico molecular modeling studies against -ketoacyl-ACP reductase (MabA) (PDB ID: IUZN) and pantothenate kinase (PanK) (PDB ID: ; 3AF3). Compounds 5a, 5c, 5d, and 6c, which had docking scores of -8.29, -8.36, -8.17 and -7.39 kcal mol(-1), respectively, displayed interactions with MabA that were better than those of isoniazid (-6.81 kcal mol(-1)). Similarly, compounds 5a, 5c, 5d, and 6c, which had docking scores of -7.55, -7.64, -7.40 and -6.7 kcal mol(-1), respectively, displayed interactions with PanK that were comparable to those of isoniazid (-7.64 kcal mol(-1)). Because of their docking scores, these compounds were screened in vitro against Mycobacterium tuberculosis H37Ra (Mtb) using an XRMA protocol. Among the screened compounds, the dihydrorugosaflavonoid derivatives 5a, 5c, and 5d had IC50 values of 12.93, 8.43 and 11.3 g mL(-1), respectively, and exhibited better inhibitory activity than the parent rugosaflavonoid derivatives. The rugosaflavonoid derivative 6c had an IC50 value of 17.57 g mL(-1). The synthesized compounds also displayed inhibitory activity against the Gram-positive bacteria Bacillus subtilis and Staphylococcus aureus. The present study will be helpful for the further development of these molecules into antitubercular lead candidates.